Intra-species Space Competition in Cocoa Ecosystem: Invader Ants’ Geovisualisation (Journal of the Bangladesh Agricultural University, 2024)
The Malaysian Cocoa Board (MCB) has conducted numerous research and development activities to ensure the cocoa industry's sustainability. One of the essential aspects is the management of pests and diseases of cocoa. A qualitative study to detect the relationship between presences of biological control agents, Cocoa Black Ant (CBA) against the major pest of cocoa (Cocoa pod borer, CPB) with other ants' intrusion was done with the aid of geospatial mapping and analysis approaches. Other species of ants (ant invades) will affect the availability of CBA in controlling CPB infestation. Thirty months of data collection comprised two different blocks; Blocks 10B and 18A were used as the study area. Analysis of the differences and similarities of other ant's intrusion for each block and Plots was performed to understand the behavior and distribution pattern. Four different methods were introduced; Plot A was augmented with one artificial ant nest for every two cocoa trees, Plot B had one nest on every single cocoa tree, Plot C had two nests on every single cocoa tree, and Plot D without an artificial nest. The study reveals that the highest or lowest CBA populations and distribution could induce a strong, reasonable relationship against other ant types. Plots with artificial ant nests (A, B, and C) showed low intrusion rates with a ratio of 1:1 for Plot B indicated the best result, whereas, Plot without artificial ant nest (Plot D) the highest rate of intrusion during the months and years of observation. The findings in this research provide a new indicator of the ants' species interaction using temporal geospatial-based mapping and analysis within a cocoa plantation ecosystemJ Bangladesh Agril Univ 19(1): 30–36, 2021https://doi.org/10.5455/JBAU.37944